Failure to detect HLA-A*6802-restricted CD8(+) T cells specific for Chlamydia trachomatis antigens in subjects from trachoma-endemic communities - Mahdi, O S M (Blackwell Science Inc, 2001)
The role of HLA-A*6802-restricted CD8(+) T cells in chlamydial disease was investigated in human ocular infections. Peptides with predicted binding motifs for HLA-A*6802 were synthesized using sequences based on chlamydial antigens, major outer membrane protein (MOMP), macrophage infectivity potentiator (MIP) and heat shock protein (hsp70). Peptides were pooled according to Chlamydia trachomatis protein type and serovar, and were tested in (51)Cr-release cytotoxic T lymphocyte (CTL) and enzyme-linked immunospot (ELISPOT) assays, using peripheral blood mononuclear cells (PBMC) isolated from subjects living in trachoma-endemic communities in The Gambia. Significant CTL activity or interferon-gamma release was not detected in any of the subjects, suggesting either that HLA-A*6802 CD8(+) T cells may not be important in ocular infections or that the peptides chosen did not represent epitopes.